Why Only Manage POTS?!? POTS MAY BE CURED!! A Review - NL, DePace; MI, Weintraub; Munoz; R; K, Kaczmarski; R, Manno; G, Ahmed; J, Colombo (Cardiology and Cardiovascular Medicine, 2024)
Postural Orthostatic Tachycardia Syndrome (POTS) is but a type of Dysautonomia. The Dysautonomia describes the other symptoms that are usually associated with POTS, but not due to POTS. Through Dysautonomia, POTS is thereby also a symptom of many other disorders, including Long- COVID, PTSD, Anxiety, EDS/Hypermobility, and many more. The ‘O’ in POTS is the autonomic dysfunction. The ‘T’ in POTS is perceived as a symptom; however, it is truly a compensatory mechanism. A primary problem with POTS and its diagnosis is that in ⅓ to ½ of the POTS patient population, depending on history, POTS is comorbid with Vasovagal Syncope (VVS). Patients do not faint from POTS. POTS is compensated. Patients do faint from VVS. The problem is the fact that the Orthostatic dysfunction in POTS is a Sympathetic dysfunction and the Vagal component in VVS is a Parasympathetic dysfunction. Most current autonomic monitoring techniques are not able to differentiate Sympathetic from Parasympathetic function without assumption or approximation. Unfortunately, the accepted assumptions and approximations are not valid in younger patients which characterize most POTS patients. Herein, we introduce an autonomic monitoring technique, P&S Monitoring, that is able to mathematically independently and simultaneously measure and differentiate Parasympathetic from Sympathetic activity, as well as alpha Adrenergic (α-Sympathetic) from beta-Adrenergic (β-sympathetic) activity. With P&S Monitoring POTS and VVS are able to be differentiated, identified even if comorbid, and treated in a classical or standard manner and both dysfunctions relieved concurrently; thereby helping to restore patient’s quality of life and productivity.